Oral and oropharyngeal cancer surgery with free-flap reconstruction in the elderly: Factors associated with long-term quality of life, patient needs and concerns. A GETTEC cross-sectional study. (December 2020) - Bozec, Alexandre; Majoufre, Claire; De Boutray, Marie; Gal, Jocelyn; Chamorey, Emmanuel; Roussel, Lise-Marie; Philouze, Pierre; Testelin, Sylvie; Coninckx, Marine; Bach, Christine; Schultz, Philippe; Garrel, Renaud; et al.
Abstract: Objectives: To assess the factors associated with long-term quality of life (QoL) and patient concerns in elderly oral or oropharyngeal cancer (OOPC) patients after oncologic surgery and free-flap reconstruction. Methods: Patients aged over 70 years who were still alive and disease-free at least 1 year after surgery were enrolled in this cross-sectional multicentric study. Patients completed the EORTC QLQ-C30, -H&N35 and -ELD14 QoL questionnaires, and the Hospital Anxiety and Depression Scale (HADS). Patient needs were evaluated using the Patient Concerns Inventory (PCI). Factors associated with these clinical outcomes were determined in univariate and multivariate analysis. Results: Sixty-four patients were included in this study. Long-term QoL, functioning scales and patient autonomy were well-preserved. Main persistent symptoms were fatigue, constipation and oral function-related disorders. Salivary and mastication/swallowing problems were the main patient concerns. The mean number of patient concerns increased with the deterioration of their QoL. Psychological distress (HADS score ≥ 15) and patient frailty (G8 score < 15) were significantly associated with poor QoL outcomes. Conclusions: We found a negative correlation between the number of patient concerns and QoL. Dental rehabilitation and psychological and nutritional supportive measures are of critical importance in the multidisciplinary management of elderly OOPC patients. Highlights: Long-term QoL, functioning scales and patient autonomy were well-preserved. Main persistent symptoms were fatigue, constipation and oral function-related disorders. The mean number of patient concerns increased with the deterioration of their QoL. Psychological distress and patient frailty were associated with poor QoL outcomes.